(untitled) (Caderno de Pesquisa, 2012)
The possibility of remediating contaminated soils through the use of high biomass-generating, native plant species capable of removing heavy metals is receiving increased attention. The capacity of accumulation cadmium (Cd) of Atriplex halimus was tested by growing transplanted specie in a pine bark compost substrate (pH 5.6) contaminated with 100 mg Cd kg-1. After 70 days, the increase in biomass in the plant enhanced the phytoextraction of Cd. The leaf Cd concentration reached 35 mg Cd kg-1. The normal growth shown by this specie in the presence of high concentration of Cd and under conditions of high temperature and acidic pH, suggests that this specie may be used to generate a green cover on soils contaminated by metals and may contribute to their remediation.